Hubungan Antara Kemampuan Membaca Pemahaman Dengan Hasil Belajar Siswa Kelas IV SD Negeri 71 Kota Bengkulu - Dian Tiara Kesuma; Nani Yuliantini; Irfan Supriatna (JURIDIKDAS, 2021)
This study aims to find out the relationship between reading comprehension and learning outcomes of 4th grade students at SDN 71 Bengkulu. The type of research used in this study is quantitative correlationonal. The population in this study is all 4th grade students of SD Negeri 71 Bengkulu with sampling techniques, namely total samples. The data collection techniques used are tests and documentation. Tests are instrumens for measure reading comprehension and documentation is to collect data on students' learning outcomes. The analysis techniques used are descriptive static analysis and hypothesis testing using the pearson product moment correlation formula. The result of correlation calculation shows a positive correlation coefficient of 0.528 and rtable at a significance level of 5% is 0.219. So, rcalculates>rtable, i.e. 0.528 > 0.219, Ha is accepted and Ho is rejected. R Square test is conducted to find out the contribution of variable x to variable y. The result from the R Square test showed that the coefficient of determination was 27.9%. Based on the analysis that has been done, it can be concluded that there is a significant relationship between the reading comprehension and the learning outcomes of 4th grade students of SD Negeri 71 Bengkulu.